2008
DOI: 10.1620/tjem.215.333
|View full text |Cite
|
Sign up to set email alerts
|

.BETA.-Phenylethylamine Inhibits K+ Currents in Neocortical Neurons of the Rat: A Possible Mechanism of .BETA.-phenylethylamine-induced Seizures

Abstract: β -Phenylethylamine (β -PEA), an endogenous amine synthesized in the brain, serves as a neuromodulator and is involved in the pathophysiology of various neurological disorders such as depression, schizophrenia, and attention-deficit hyperactivity disorder. β -PEA fully exerts the physiological effects within the nanomolar concentration range via the trace amine receptors, but β -PEA also causes convulsions at much higher concentrations via an as yet unknown mechanism. To investigate the electrophysiological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…AMPA receptors regulate calcium oscillation frequency, while mgluR regulates frequency and amplitude as well as release of intracellular calcium stores via phospholipase C (PLC). Thus, the bioactivity of the credneramides in this assay could be due to modulation of AMPA, mgluR, or PLC signaling or to TAAR1, dopamine, and GABA receptor activity; the latter three are known to be modulated by PEA. Unlike grenadamide A, a mixture of 1 and 2 did not possess cannabinoid receptor binding activity, and only marginal cytotoxic activity against the beet armyworm Spodoptera exigua was reported for grenadamides B and C, which are structurally most similar to the credneramides …”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…AMPA receptors regulate calcium oscillation frequency, while mgluR regulates frequency and amplitude as well as release of intracellular calcium stores via phospholipase C (PLC). Thus, the bioactivity of the credneramides in this assay could be due to modulation of AMPA, mgluR, or PLC signaling or to TAAR1, dopamine, and GABA receptor activity; the latter three are known to be modulated by PEA. Unlike grenadamide A, a mixture of 1 and 2 did not possess cannabinoid receptor binding activity, and only marginal cytotoxic activity against the beet armyworm Spodoptera exigua was reported for grenadamides B and C, which are structurally most similar to the credneramides …”
Section: Resultsmentioning
confidence: 91%
“…2831 By binding to these receptors, PEA derivatives modulate higher cognitive function via a capacity to act as hallucinogens, stimulants, and antidepressants. 28,29 This class of compounds has also been implicated in the pathogenesis of several neurologic diseases including depression, attention deficit and hyperactivity disorder (ADHD), and schizophrenia. 28,29,32 Given the substantial evidence of neuromodulation by phenethylamines, the neuromodulatory effects of credneramide A ( 1 ) are reasonable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the negative regulation of D 2 autoreceptor function by TA contributes to the regulation of the normal basal activity of dopaminergic cells, and it might also render them more excitable. An excitatory effect of TAs on cortical and subthalamic neurones has been described previously (Zhu et al ., 2007; Kitamura et al ., 2008) and it was demonstrated that β‐PEA inhibits K + currents in neocortical neurones of the rat (Kitamura et al ., 2008). TA‐induced blunting of D 2 autoreceptor inhibition has potentially important implications for the control of movement, reward, mood, motor function and cognition and, consequently, may be pertinent to the aetiology and treatment of diseases in which perturbed dopaminergic transmission has been implicated, such as schizophrenia, drug abuse, depression, Parkinson's disease and attention deficit hyperactive disorders (Boulton, 1980; Davis and Boulton, 1994; Bergman et al ., 2001; Millan, 2006; Sotnikova et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%